Innovaciones tecnológicas aplicadas al transporte colectivo en Quito. Optimización en la evaluación de la demanda con GPS y SIG - Florent Demoraes; Francis Bondoux; Marc Souris; Hidalgo Núñez (Bulletin de l'Institut Français d'Études Andines, 2004)
This paper serves three purposes. First, to detail FINDEM, an on-board system developed in Quito, which integrates a GPS and allows a semi-automatic passengers’ counting within an urban transportation network. Second, to present the methodology about the processing of the data collected with this equipment using a Geographical Information System called SAVANE. Third, to give the main results of a first “Getting On-Off” survey carried out with FINDEM on buses, along the “Quito - El Quinche” suburban corridor.